Spontaneous bilateral chronic subdural haematoma in an 8-month-old male with osteogenesis imperfecta: A case report - Ekpene UU; Uduehe EE; Isobara I; Ndafia N (Ibom Medical Journal)
Osteogenesis imperfecta is a rare inherited collagen disease that presents most commonly with increased bone fragility. We present an 8-month-old male child with a 5-month history of progressive abnormal increase in the size of the head and a history of multiple long bone fractures not preceded by trauma and blue sclerae. Cranial CT scan showed bilateral frontoparietal chronic subdural haematoma. X-rays of the limbs showed healed left humeral and right femoral fractures.